ARBITRATION AND COURT-LIKE MECHANISMS IN INVESTMENT LAW: A PARADIGM SHIFT IN RESOLVING INVESTORS’ DISPUTES - Dirani, Mostafa; Hassoun, Rawan (International Journal of Engineering Technologies and Management Research, 2024)
This paper examines the movement in paradigm towards arbitration as a means of settling conflicts between investors in the field of investment law. The research evaluates the efficacy, equity, and influence of arbitration on state sovereignty and investor rights by examining the feedback of 300 professionals engaged in investment arbitration, such as lawyers, arbitrators, and legal academics. The quantitative analysis provides an impartial assessment of the success of arbitration in comparison to traditional litigation, emphasising its perceived efficiency and flexibility. Nevertheless, apprehensions regarding its influence on state sovereignty and divergent perspectives on equity and safeguarding of investors are apparent. The report also analyses the impact of worldwide economic and legal patterns on arbitration processes and predicts forthcoming modifications prompted by inclusion, technology, and legislation. Arbitration encounters difficulties in upholding impartiality, transparency, and accountability, notwithstanding its advantageous aspects. The results indicate the necessity for continuous adjustment and flexibility to address changing global circumstances and legal norms. This study enhances comprehension of international investment law by providing valuable perspectives on the present condition and future direction of arbitration as a means of resolving disputes.